2003
DOI: 10.1017/s0022112003005500
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulations of turbulent channel flow with transverse square bars on one wall

Abstract: Direct numerical simulations have been carried out for a fully developed turbulent channel flow with a smooth upper wall and a lower wall consisting of square bars separated by a rectangular cavity. A wide range of w/k, the cavity width to roughness height ratio, was considered. For w/k > 7, recirculation zones occur immediately upstream and downstream of each element while mean streamlines and spatial distributions of the skin frictional drag indicate that each element is virtually isolated. The maximum form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
279
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(344 citation statements)
references
References 10 publications
61
279
0
4
Order By: Relevance
“…It is shown in figures 8(a) & (b) that the behaviour of the roughness length as a function of frontal and plan solidity is drastically different. Figure 8(a) shows that the roughness length (which is related to the total drag) increases in the sparse regime, and indicates a marginal decrease after the peak for increased values of frontal solidity, as in Leonardi et al (2003) and Leonardi & Castro (2010). Within the range of solidity explored herewith, the bulk drag seems to reach a peak at λ F = 0.21 for a fixed λ P = 0.27.…”
Section: Effect Of Surface Morphology On Aerodynamic Parametersmentioning
confidence: 78%
“…It is shown in figures 8(a) & (b) that the behaviour of the roughness length as a function of frontal and plan solidity is drastically different. Figure 8(a) shows that the roughness length (which is related to the total drag) increases in the sparse regime, and indicates a marginal decrease after the peak for increased values of frontal solidity, as in Leonardi et al (2003) and Leonardi & Castro (2010). Within the range of solidity explored herewith, the bulk drag seems to reach a peak at λ F = 0.21 for a fixed λ P = 0.27.…”
Section: Effect Of Surface Morphology On Aerodynamic Parametersmentioning
confidence: 78%
“…This position is located at x/D h = 28, where x is the distance of the seventh rib from the inlet, and D h is the hydraulic diameter of the channel. According to Leonardi et al [3], the roughness elements are virtually isolated as the cavity width to roughness height ratio is greater than 7 (or the pitch ratio is greater than 8). Throughout this paper, reference quantities for length and velocity are e and U 0 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Even though numerous studies have been carried out to study the thermal and flow characteristics in ribbed channels, the understanding of this phenomenon is not complete. In direct numerical simulations (DNS) of turbulent channel flow with square ribs on one wall, Leonardi et al [3] showed that main flow features, such as the size and strength of the recirculation zones, do not change significantly and reoccur along the channel as the cavity width to roughness height ratio is greater than 7. Using liquid crystals, Rau et al [4] found a second maximum of heat transfer rate as the rib pitch ratio is greater than 10.…”
Section: Introductionmentioning
confidence: 99%
“…Probability of negative u versus wall-normal coordinate z for different Reynolds numbers: (a) graphite case and (b) grit-blasted case. (Maass & Schumann 1994;Cherukat et al 1998;Leonardi et al 2003;Napoli et al 2008). For the current surfaces, the situation is more complex, since the surfaces also show variations in the transverse direction, which allows the near-wall flow to circumnavigate some of the roughness features.…”
Section: Reverse Flowmentioning
confidence: 99%